Shariah law and Hudud : understanding its objectives and spirit - Mohamed Ali (2014)
The Sultan of Brunei recently announced the introduction of the Shariah penal code or hudud as part of implementing Shariah law in the country. What do the terms Shariah law and Hudud entail and what are their objectives?